(untitled) (Journal of Science and Technology, 2015)
The role of surgery in the management of complications of measles ’IBS been high-lighted with three cases-observations at the Komfo Anokye Teaching Hospital, Kumasi, Ghana, as follows: (1)concurrent osteomyelitis of a rib, p:m-pneumothorax, pyo-pneurnoperitoneum has been successful treated with simultaneous thoracotomy and laparotomy, as well as underwater seal drainage and sequestrectomy. (2) strictures and stenosis of the mouth have been amenable to release, of contracture and cheiloplasty. (3) massive subcutaneous emphysema which can be associated ectropion of the eyelids can heal spontaneously without surgery if not concomitant with pneumato-rax.